تصميم نظام تحكم ألي لمحطة تبريد باستخدام المتحكمات الضبابية. - بلال شيحا; أحمد رضا (Tishreen University, 2019)
This paper deals with design of an expert system to control cooling unit operations based on Programmable Logic Controllers (PLC) and fuzzy logic controllers (FLC). The proposed expert system depend mainly on using the concept of fuzzy logic to design the controllers and include the way of human thinking in the process of operations control through  using a set of (If - Then) rules. This research presents the methods of starting and protecting of induction motors witch drive the fans that are used to cool the water, and it presents the design of fuzzy controller that are used to control of water level in the main tank through determine the percentage of opening both Makeup and drain valves depending on the water level, and presents design of fuzzy controller that are used with pumps to maintain the out pressure around specific value which insure the delivery of cooled water to other units where it used in heat exchange process, this controller's feedback signal presents incoming signal for variable speed driver(VSD)that responsible for changing the speed of the pump. The fuzzy controllers were built with MATLAB, and the results of the test showed the efficiency of using these controls in the processes that require maintaining the level of liquid and control the speed of the rotor part of the pumps. تصميم نظام تحكم ألي لمحطة تبريد باستخدام المتحكمات الضبابية. تقترح هذه المقالة تصميم نظام خبير للتحكم بالعمليات في وحدة تبريد بالاعتماد على المتحكمات المنطقية القابلة للبرمجة (PLC) والمتحكمات الضبابية(FLC) . يعتمد النظام الخبير المقترح على استخدام مفهوم المنطق الضبابي لتصميم المتحكمات التي تتيح بدورها تضمين خبرة المشغلين وطريقة التفكير البشرية في التحكم بسير العمليات من خلال القواعد (If - Then). يعرض هذا البحث طرق التحكم بإقلاع وحماية المحركات الحثية التي تقود المراوح المستخدمة لتبريد الماء, كما يعرض تصميم المتحكم الضبابي المستخدم للتحكم بمستوى المياه في الخزان الرئيسي من خلال تحديد نسبة فتح صمام التعويض (Make up Valves) وصمام الهدر (Drain Valves), وتصميم المتحكم الضبابي المستخدم مع المضخات بهدف الحفاظ على ضغط مياه خارج حول قيمة محددة تضمن وصول المياه المبردة إلى بقية الأقسام حيث يجري استخدامها في عملية التبادل الحراري, وتمثل إشارة خرج هذا المتحكم إشارة دخل لمغير السرعة Variable Speed Driver (VSD) المسؤول عن تغيير سرعة عمل المضخة. تم بناء المتحكمات الضبابية من خلال برنامج MATLAB, وأظهرت نتائج الاختبار كفاءة استخدام هذه المتحكمات في العمليات التي تتطلب الحفاظ على مستوى السائل والتحكم بسرعة الجزء الدائر للمضخات.